Specialized banks systems with using of vpn technology - Turchinov, A. A.; Khakhanova, I. V. (My University, 2019)
Specialized systems are an integral part of modern banks. Using such systems, you can quickly and safely transmit and receive information. They provide communication between computers and specialized technologies of the same enterprise,located within the same building or geographically distributed. There are several ways to build such systems.
Keywords: virtual network; transfer security; security of information; logistics structures built